Effects of Azospirillum inoculation on sweetpotato grown on sandy tin‐tailing soil - Saad, M. S.; Sabuddin, A. S. Ali; Yunus, A. G.; Shamsuddin, Zulkifli H. (Marcel Dekker Inc., 1999)
Sweetpotato [Ipomoea batatas (L.) Lam.], the second most important root crop in Malaysia after cassava, is grown mainly on marginal soils such as peat and sandy tin-tailing. The sandy tin-tailing soil, with more than 90% sand, requires higher fertilizer input. Thus, the cost of crop production on such soil can be very expensive when the prize of fertilizer increases. The use of bio-fertilizer such as the nitrogen (N)-fixing bacteria can reduce fertilizer application and consequently reduces production cost. This study was undertaken to investigate the possibility of using Azospirillum brasilense to replace N fertilizer for sweetpotato variety UPMSS5 production on sandy tin-tailing soil. Three strains of A. brasilense, namely sp7, UPMB12, and UPMB14 were used. They were inoculated with and without N fertilizer application at 1/3 (33 kg N ha-1) of the 100 kg N ha-1 recommended for sweetpotato production on sandy soils. The results showed that plants inoculated with Azospirillum produced similar or higher root yield, vigorous vegetative growth, and higher N content in the roots and leaves than plants given normal rate of N fertilizer. The Azospirillum inoculation was more effective when initial N fertilizer at one-third of the recommended rate was applied at one week after planting. The Azospirillum strain UPMB14 was more compatible with the variety UPMSS5. Plant treated with this strain, added with at 1/3 N at one week after planting, produced 27.2 t ha-1 of root yield or about 74% higher than the control (15.6 t ha-1). It was concluded that Azospirillum is a potential bio-fertilizer for sweetpotato grown on sandy soils. However, more compatible strains should be used for specific sweetpotato variety. Application of initial N fertilizer at 1/3 or less of the recommended N rate is recommended to supply the N requirement at the early stage of crop growth before the commencement of the beneficial effect of the Azospirillumplant root association.